Network Video Monitoring System of Wind Farm Based on Network Digital Speed Dome Camera - XIA Xiangchun (Kongzhi Yu Xinxi Jishu)
Taking the video monitoring system of Chenzhou Yangtianhu Wind Farm of Hunan as an example, this paper introduces a novel design scheme of video monitoring system based on network digital speed dome camera. It analyzes and discusses the network design and lightning protection, and can provide certain reference for the design of video monitoring system of wind farm.